Ureterocele as differential diagnosis of hydrosalpinx-an interesting case from the clinical practice - Psilopatis, Iason; Beckmann, Matthias; Emons, Julius; Schulmeyer, Carla (Journal of Surgical Case Reports, 2024)
Hydrosalpinx is a common condition in women of reproductive age that correlates with infertility. A ureterocele is a dilatation of the terminal ureter within the bladder and/or urethra that occurs seldomly in adults, but can sonographically be mistaken for a hydrosalpinx.We report of a 29-year-old patient (G2/P1) who was referred in our department with secondary infertility and suspicion of hydrosalpinx.Intraoperatively,no hydrosalpinx could be visualized.Postoperatively,an intravesical cystic mass was detected,alongside a second-degree urinary retention. Sonographically, a double kidney on the left side and an accentuated calyx system could be diagnosed. Ureteroceles seem to represent a rare but still possible differential diagnosis in suspected hydrosalpinx, given the similar sonographic presentation of both conditions.
CRIS-Team Scopus Importer:2024-04-26
Keywords: hydrosalpinx; infertility; ureterocele